Diagnosis of African trypanosomosis - Masake, R.A. (OAU, 1995)
Diagnosis is an essential requirement in the management of disease both at the level of the individual, when a decision has to be made whether to treat or not, and at the epidemiological level for evaluating the performance of disease control strategies. The centrality of diagnosis in disease management has, therefore led to introduction of a variety of tests for detection of trypanosome infection. The standard parasitological techniques routinely applied in the field are not sufficiently sensitive despite the significant improvements made on them over the years. In view of this the more sensitive indirect immunofluorescence antibody detection test (IFAT), enzyme-linked immunoassay (ELISA) and card agglutination assays (CATT) were developed for revealing the presence of anti-trypanosome antibodies. Unfortunately antibody detection tests have several shortcomings including the lack of defined antigens common to all trypanosomes, inapplicability of these assays in the field in their current format and finally recognition of the fact that presence of antibody cannot always be equated with presence of trypanosome infection. In an effort to come up with technologies which are likely to give accurate information on current status of infection, techniques are in place for trapping trypanosome antigens (ag-ELISA) and amplifying trypanosome DNA (PCR). These new technologies, with a bit of improvement, are likely to revolutionalise diagnosis of trypanosomosis in animals, man and tsetse flies.